A high-rate biomass hard carbon material and its preparation method and application
By using vanillic acid to reconstruct the oxygen functional groups of the biomass hard carbon material in the negative electrode material of sodium ion battery, the problems of slow reaction kinetics and capacity attenuation of existing materials are solved, and materials with high magnification, cycle stability and excellent electrochemical properties are achieved.
Patent Information
- Application Number
- CN202410431881.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-04-11
AI Technical Summary
The existing sodium ion battery anode materials have problems with slow reaction kinetics and capacity attenuation, and the preparation process of hard carbon materials is single and lacks rich exploration.
The surface oxygen functional groups of the biomass hard carbon material are reconstituted by vanillic acid to prepare a high-ratio biomass hard carbon material. This material is reconstructed by carbonization of biomass raw materials and oxygen functional groups to form a material with stable structure and high conductivity.
The material's conductivity and cycle stability are improved, and its rate performance is excellent, making it show high specific energy, high power and excellent cycle performance in the negative electrode applications of sodium ion battery.
Smart Images

Figure CN118343729B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a high-rate biomass hard carbon material and a preparation method and application thereof. Background Art
[0002] At present, electrochemical energy storage technology has become the most promising energy storage technology due to its high conversion efficiency, long service life, safety and convenience. It is also the trend of energy storage in today's society. Among many chemical power sources, lithium-ion batteries have firmly occupied the energy storage market due to their high energy density and cycle stability, and are widely used in various electronic devices, new energy electric vehicles and military drones. However, lithium is a scarce element, accounting for only 0.0017% of the weight of the earth's crust. In the near future, it is very likely to face a "lithium crisis". The uneven geographical distribution of lithium deposits will make this crisis more serious.
[0003] Sodium and lithium belong to the first main group, and their chemical properties are very similar. Sodium-ion batteries work in a similar way to lithium-ion batteries, and are less difficult to develop. At the same time, with the advantages of large sodium reserves and low cost, they are the most promising alternative technology in many systems and have become a strong candidate in the field of large-scale energy storage. However, in current practical applications, sodium-ion battery negative electrode materials often face problems such as slow reaction kinetics and severe capacity attenuation caused by volume expansion of electrode materials due to large ion size during charging and discharging. Hard carbon materials have a highly disordered structure and rich defects and microporous structures; at the same time, the larger interlayer spacing is also conducive to the transmission of sodium ions. At the same time, they have many advantages such as wide sources, low preparation cost, non-toxicity, and good thermal stability, and have high practical application value.
[0004] Important properties of sodium-ion batteries, such as energy density, rate performance and cycle life, are closely related to the negative electrode materials. The key to improving the performance of hard carbon materials lies in the composition and micro-nanostructure of the materials. However, during the research process, it was found that the current preparation process for hard carbon materials is relatively simple, and there is a lack of more extensive exploration of material system selection and process design. The ion diffusion coefficient of the material and its rate performance limit its further development. Therefore, it is urgent to develop hard carbon materials and efficient preparation processes with low cost, simple process and excellent electrochemical performance. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a high-rate biomass hard carbon material and a preparation method and application thereof. The biomass hard carbon material is prepared by reconstructing the surface oxygen functional groups of the material with vanillic acid. The obtained biomass hard carbon material has a large specific capacity and excellent rate performance, and can be used in sodium ion batteries.
[0006] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:
[0007] A method for preparing a high-rate biomass hard carbon material comprises the following steps:
[0008] Step 1, selecting biomass raw materials, washing, drying, ball milling, and hydrochloric acid pickling to obtain precursor powder;
[0009] Step 2, subjecting the precursor powder to high-temperature carbonization treatment under an inert gas, and then naturally cooling it to room temperature to obtain a preliminary carbonized powder;
[0010] Step 3, adding the preliminary carbonized powder and vanillic acid into deionized water, heating and stirring until the water evaporates, and then drying at high temperature to obtain a high-rate biomass hard carbon material, wherein the amount of vanillic acid added is 5-20% of the mass of the preliminary carbonized powder.
[0011] As an improvement, the biomass includes one or more of tree branches, coconut shells, straw, walnut shells, wheat shells, peanut shells, bagasse, and waste paper.
[0012] As an improvement, the drying temperature of the biomass raw material in step 1 is 120-140° C. and the drying time is 24-36 hours. It should be pointed out that too low a drying temperature and / or too short a drying time will increase the difficulty of ball milling.
[0013] As an improvement, in step 1, the ball mill speed is 420-480 r / min, and the ball milling time is 2-4 h. It should be pointed out that too low a speed and / or too short a ball milling time will result in the precursor powder particles being too large and uneven.
[0014] As an improvement, the hydrochloric acid concentration in step 1 is 1-3 mol / L, and the pickling time is 36-48 hours. It should be pointed out that if the hydrochloric acid concentration is too low and / or the pickling time is too short, it will be difficult to remove impurities in the material and affect the electrochemical performance. If the hydrochloric acid concentration is too high and the pickling time is too long, it will cause excessive hydrolysis of cellulose, hemicellulose and lignin, affecting the formation of pore structure during carbonization.
[0015] As an improvement, in step 2, the inert gas is argon, nitrogen or a mixture of the two, and the flow rate of the inert gas is 40-80 mL / min.
[0016] As an improvement, the temperature of the high temperature carbonization treatment in step 2 is 1100-1400°C, the time is 2-4h, and the heating rate is 3-6°C / min. It should be pointed out that insufficient carbonization temperature and / or carbonization time will lead to undesirable pore structure and poorly stacked CC aromatic structure; too high carbonization temperature will make the interlayer of hard carbon material too small, which is not conducive to the transmission of sodium ions.
[0017] As an improvement, the temperature of heating and stirring in step 3 is 80-100°C; the temperature of high-temperature drying is 140-160°C, and the time of high-temperature drying is 12-24h. It should be pointed out that too much vanillic acid will form a thick vanillic acid layer on the surface of the material. The larger thickness will lead to high internal resistance and increased ion transfer resistance, and will block the pores and affect the transmission of sodium ions. Too little proportion will lead to unclear effect. The high-temperature drying process plays a role in dehydration condensation. Too low temperature and / or too short time will lead to incomplete reaction and affect the reconstruction of oxygen functional groups.
[0018] The high-rate biomass hard carbon material prepared by the above preparation method.
[0019] As an improvement, the high-rate biomass hard carbon material has a rod-like structure.
[0020] The application of the high-rate biomass hard carbon material prepared by the above preparation method in the preparation of sodium ion battery negative electrode.
[0021] As an improvement, the sodium ion battery negative electrode includes a carrier and a coating layer uniformly coated on the carrier, the carrier is in sheet form, and the coating layer includes a conductive agent, a binder and the above-mentioned high-rate biomass hard carbon material.
[0022] A further improvement is that the mass ratio of the conductive agent, the binder and the high-rate biomass hard carbon material is 1:1:8.
[0023] As an improvement, the carrier is copper foil, carbon-coated copper foil or carbon paper.
[0024] As an improvement, the conductive agent is Super-P, and the binder is a PVDF solution with a mass fraction of 5%.
[0025] A sodium ion battery comprises the sodium ion battery negative electrode described in the above application.
[0026] Beneficial effects:
[0027] Compared with the prior art, the high-rate biomass hard carbon material and its preparation method and application in the present invention have the following advantages:
[0028] 1. The raw materials of the preparation method of the present invention are widely available, cheap and easy to obtain, the preparation process is simple, environmentally friendly, and can be applied to large-scale production.
[0029] 2. The present invention reconstructs the oxygen functional groups on the surface of the hard carbon material through vanillic acid and introduces reversible carbonyl bonds into the surface of the material. The prepared high-rate biomass hard carbon material has a stable structure and its morphology is well preserved after grinding.
[0030] 3. The high-rate biomass hard carbon material of the present invention improves the conductivity of the material and provides abundant active sites for sodium ion storage. As the negative electrode of a sodium ion battery, it has excellent rate performance and cycle stability and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a flow chart of a method for preparing a high-rate biomass hard carbon material according to the present invention;
[0032] Figure 2 This is the SEM spectrum of the citrus tree branch-derived hard carbon material prepared in Example 1;
[0033] Figure 3 This is the TEM spectrum of the citrus tree branch-derived hard carbon material prepared in Example 1;
[0034] Figure 4 This is the XPS spectrum of the citrus tree branch-derived hard carbon material prepared in Example 1;
[0035] Figure 5 This is a first cycle charge and discharge curve of a citrus tree branch derived hard carbon material prepared in Example 1;
[0036] Figure 6 This is a rate performance diagram of a citrus tree branch derived hard carbon material prepared in Example 1;
[0037] Figure 7 This is a cycle performance diagram of a citrus tree branch-derived hard carbon material prepared in Example 1. DETAILED DESCRIPTION
[0038] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0039] The present invention uses biomass as the precursor of hard carbon materials. After carbonization, cellulose, hemicellulose and lignin form a rich porous structure and contain abundant defects after carbonization, thereby generating more sodium ion transmission pathways and storage locations. The oxygen functional groups on the surface of the hard carbon are reconstructed by vanillic acid, and more reversible carbonyl bonds are introduced. In the hard carbon material, not only the conductivity can be improved, but also defects can be introduced to generate active sites and increase the capacity. As the negative electrode of the sodium ion battery, it exhibits excellent electrochemical performance.
[0040] A method for preparing a high-rate biomass hard carbon material, referring to Figure 1 The process includes the following steps:
[0041] Step 1, selecting biomass raw materials, washing, drying, ball milling, and hydrochloric acid pickling to obtain precursor powder;
[0042] Step 2, subjecting the precursor powder to high-temperature carbonization treatment under an inert gas, and then naturally cooling it to room temperature to obtain a preliminary carbonized powder;
[0043] Step 3, adding the preliminary carbonized powder and vanillic acid into deionized water, heating and stirring until the water evaporates, and then drying at high temperature to obtain a high-rate biomass hard carbon material, wherein the amount of vanillic acid added is 5-20% of the mass of the preliminary carbonized powder.
[0044] As an improvement, the biomass in step 1 includes one or more of tree branches, coconut shells, straw, walnut shells, wheat shells, peanut shells, bagasse, and waste paper.
[0045] As an improvement, the drying temperature of the biomass raw material in step 1 is 120-140° C. and the drying time is 24-36 hours. It should be pointed out that too low a drying temperature and / or too short a drying time will increase the difficulty of ball milling.
[0046] As an improvement, in step 1, the ball mill speed is 420-480 r / min, and the ball milling time is 2-4 h. It should be pointed out that too low a speed and / or too short a ball milling time will result in the precursor powder particles being too large and uneven.
[0047] As an improvement, the hydrochloric acid concentration in step 1 is 1-3 mol / L, and the pickling time is 36-48 hours. It should be pointed out that if the hydrochloric acid concentration is too low and / or the pickling time is too short, it will be difficult to remove impurities in the material and affect the electrochemical performance. If the hydrochloric acid concentration is too high and the pickling time is too long, it will cause excessive hydrolysis of cellulose, hemicellulose and lignin, affecting the formation of pore structure during carbonization.
[0048] As an improvement, in step 2, the inert gas is argon, nitrogen or a mixture of the two, and the flow rate of the inert gas is 40-80 mL / min.
[0049] As an improvement, the temperature of the high temperature carbonization treatment in step 2 is 1100-1400°C, the time is 2-4h, and the heating rate is 3-6°C / min. It should be pointed out that insufficient carbonization temperature and / or carbonization time will lead to undesirable pore structure and poorly stacked CC aromatic structure; too high carbonization temperature will make the interlayer of hard carbon material too small, which is not conducive to the transmission of sodium ions.
[0050] As an improvement, the heating temperature in step 3 is 80-100°C; the high temperature drying temperature is 140-160°C, and the high temperature drying time is 12-24h. It should be pointed out that too much vanillic acid will form a thick vanillic acid layer on the surface of the material. The larger thickness will lead to high internal resistance and increased ion transfer resistance, and will block the pores and affect the transmission of sodium ions. Too little proportion will lead to unclear effect. The high temperature drying process plays a role in dehydration condensation. Too low temperature and / or too short time will lead to incomplete reaction and affect the reconstruction of oxygen functional groups.
[0051] The high-rate biomass hard carbon material prepared by the above preparation method has a rod-like structure.
[0052] The application of the high-rate biomass hard carbon material prepared by the above preparation method in the preparation of sodium ion battery negative electrode.
[0053] The sodium ion battery negative electrode of the present invention comprises a carrier and a coating layer uniformly coated on the carrier, wherein the carrier is in a sheet shape, and the coating layer comprises a conductive agent, a binder and a high-rate biomass hard carbon material prepared by the present invention. In a specific implementation, the mass ratio of the conductive agent, the binder and the high-rate biomass hard carbon material is 1:1:8.
[0054] As an improvement, the carrier is copper foil, carbon-coated copper foil or carbon paper.
[0055] As an improvement, the conductive agent is Super-P, and the binder is a PVDF solution with a mass fraction of 5%.
[0056] Sodium ion batteries, including the above-mentioned sodium ion battery negative electrode, can achieve high specific energy, high power and excellent cycle performance.
[0057] For ease of understanding, the technical solution provided in this application is described in detail below in conjunction with specific embodiments.
[0058] Example 1
[0059] The medlar branches were peeled, ultrasonically cleaned with industrial ethanol for 30 minutes, placed in an oven, dried at 120°C for 24 hours, and then ball-milled at 450r / min for 2 hours to obtain medlar branch powder. 10g of medlar branch powder was added to a 2mol / L hydrochloric acid solution and stirred for 36 hours, then washed with anhydrous ethanol and deionized water until neutral, and dried to obtain a precursor powder;
[0060] In a tubular furnace filled with nitrogen, the temperature was raised to 1200°C at a heating rate of 5°C / min and kept for 2 hours. After natural cooling, the carbonized product and 15% vanillic acid of the product mass were heated and stirred at 80°C until the water evaporated. The product was dried at 140°C for 12 hours to obtain a hard carbon material.
[0061] The hard carbon material prepared by the above method was tested, and the SEM spectrum of the hard carbon material derived from citrus branches is as follows: Figure 2 As shown in the figure, it can be seen that the hard carbon material derived from wolfberry branches is rod-shaped and the morphology is well maintained.
[0062] TEM spectrum of the hard carbon material derived from citrus branches Figure 3 ,As can be seen from the figure, the disordered carbon layers, graphite-like domains and abundant micropores are typical ,characteristics of hard carbon.
[0063] The XPS spectrum of the hard carbon material derived from citrus branches is as follows Figure 4 As shown in the figure, it can be seen that the citrus tree branch derived hard carbon material has a high oxygen content and a high proportion of reversible carbonyl bonds, which proves that the oxygen functional groups on the surface of the material have been successfully reconstructed.
[0064] Example 2
[0065] The citrus tree branch-derived hard carbon material prepared in Example 1 was used for application experiments.
[0066] Weigh 160 mg of citrus tree branch-derived hard carbon material, 20 mg of conductive agent Super-P, and 400 mg of binder PVDF (5% mass fraction solution), fully mix them into a slurry, and evenly apply them on a copper foil with a diameter of 1.2 cm. The copper foil loaded with active materials is used as the negative electrode of the sodium ion battery.
[0067] The performance of the sodium ion battery negative electrode was tested, and the first cycle charge and discharge curve was as follows: Figure 5 , the rate performance diagram is as follows Figure 6 , cycle performance such as Figure 7 As shown. Figure 5 It can be seen that the first cycle charge and discharge curve shows a typical slope area and platform area, and the capacity of the slope area accounts for a high proportion. Figure 6-Figure 7 It can be seen that the specific capacity of the citrus tree branch-derived hard carbon material can reach 344mAh / g at 0.05A / g; at a large current density of 10A / g, it has a high specific capacity of 195mAh / g; after 3000 cycles at a current density of 10A / g, the capacity retention rate is as high as 70%, proving that the citrus tree branch-derived hard carbon has excellent electrochemical properties as a negative electrode material for sodium ion batteries.
[0068] Example 3
[0069] Except that the hydrochloric acid treatment time was changed to 36 h, the rest was the same as in Example 1.
[0070] Example 4
[0071] Except that the carbonization temperature is changed to 1100° C., the rest is the same as in Example 1.
[0072] Example 5
[0073] Except that the carbonization temperature is changed to 1300° C., the rest is the same as in Example 1.
[0074] Example 6
[0075] Except that the proportion of vanillic acid was changed to 10%, the rest was the same as in Example 1.
[0076] Example 7
[0077] Except that the heating and stirring temperature was changed to 90°C, the rest was the same as in Example 1.
[0078] Example 8
[0079] Except that the drying temperature is changed to 160° C., the rest is the same as in Example 1.
[0080] According to the steps of Example 2, the material prepared in the above example was prepared into a negative electrode, and then assembled with a metal sodium sheet into a button-type battery for the following electrochemical performance tests, wherein: (1) Cycle performance test: Under normal temperature conditions, the prepared battery was tested on a LAND battery test system, the charge and discharge voltage range was 0.01 to 2V, and the test battery was charged and discharged at a constant current density of 10A / g; (2) Rate performance test: Under normal temperature conditions, the prepared battery was tested on a LAND battery test system, and the specific capacity of the battery was tested at current densities of 0.05A / g, 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g, 5A / g, and 10A / g. The test results are shown in Table 1.
[0081] Table 1 Performance test of biomass hard carbon materials prepared by different methods as negative electrodes for sodium ion batteries
[0082]
[0083]
[0084] As shown in Table 1, using the high-rate biomass hard carbon material prepared in Example 1 as the negative electrode of a sodium ion battery can achieve better rate performance and cycle performance.
[0085] Comparative Example 1
[0086] Except that sinapinic acid is used as the surface modifier instead of vanillic acid, the rest is the same as Example 1.
[0087] Under the same test conditions as in the example, the specific capacity of the prepared hard carbon sample was only 310 mAh / g at a current density of 0.05 A / g. At a high current density of 10 A / g, the specific capacity was reduced to 140 mAh / g. Compared with the hard carbon material prepared in the example, the specific capacity is lower and the rate performance is poor.
[0088] The above is only a specific implementation of the present application. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. The protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a high-rate biomass hard carbon material, characterized in that: The following steps are involved: Step 1, selecting a biomass raw material, washing, drying, ball milling, and hydrochloric acid pickling to obtain a precursor powder, wherein the drying temperature of the biomass raw material is 120-140°C, the drying time is 24-36h, the ball mill speed is 420-480r / min, the ball milling time is 2-4h, the hydrochloric acid concentration is 1-3 mol / L, and the pickling time is 36-48h, and the biomass raw material is a citrus tree branch; Step 2, under an inert gas, subjecting the precursor powder to a high-temperature carbonization treatment, and then naturally cooling it to room temperature to obtain a preliminary carbonized powder, wherein the high-temperature carbonization treatment temperature is 1100-1400° C., the time is 2-4 hours, and the heating rate is 3-6° C. / min; Step 3, adding the preliminary carbonized powder and vanillic acid into deionized water, heating and stirring at 80-100°C until the water evaporates, and then drying at 140-160°C for 12-24 hours to obtain a high-rate biomass hard carbon material, wherein the amount of vanillic acid added is 5-20% of the mass of the preliminary carbonized powder.
2. The method for preparing a high-rate biomass hard carbon material according to claim 1, characterized in that: In step 2, the inert gas is argon, nitrogen or a mixture of the two, and the flow rate of the inert gas is 40-80 mL / min.
3. The high-rate biomass hard carbon material prepared by the preparation method according to claim 1, characterized in that: The high-rate biomass hard carbon material has a rod-like structure and a specific capacity of 195 mAh / g at a high current density of 10 A / g.
4. The use of the high-rate biomass hard carbon material on the negative electrode of a sodium ion battery according to claim 3, characterized in that: The sodium ion battery negative electrode comprises a carrier and a coating layer uniformly coated on the carrier, the carrier is in sheet form, and the coating layer comprises a conductive agent, a binder and the high-rate biomass hard carbon material according to claim 3.
Citation Information
Patent Citations
Efficient hard carbon material and preparation method and application of efficient hard carbon material
CN108682815A